Investigation of the effects of welding parameters on the tensile strength and fatigue life of the structural welded joints S355J2+N steel plate - Heyns, P.S. (Philippus Stephanus) (University of Pretoria, 2023)
Dissertation (MSc (Mechanical Engineering))--University of Pretoria, 2023.